The Phenotypic Impact of Mitochondrial DNA Mutations in Cancer - Gemin, Adam (My University, 2003)
Mitochondrial DNA (mtDNA) aberrations have been detected in a large proportion of tissue samples isolated from human tumours, although the functional significance of these mutations is yet to be determined. Proponents of the selective advantage mtDNA defect acquisition model believe these mutations arise spontaneously, but propagate because they afford some benefit to overall neoplastic cell proliferation. The most tantalizing of these growth advantage properties is an elevation of electron transport chain (ETC) generated reactive oxygen species (ROS), which are already associated with some pathogenic mtDNA defects. However, others theorize that these mutations may arise spontaneously and expand through the ambivalent process of genetic drift alone. The 2008 human ovarian cancer cell line and its cis-platinum(II)-diammine-dichloride (CDDP) resistant C13* cell variant have divergent phenotypes when mitochondrial morphology, membrane potential (ΔΨₘ), ROS production, and rate of oxygen consumption are considered. Furthermore, the increased ΔΨₘ observed in C13* cells has been implicated in its CDDP resistant characteristic. In order to determine if mtDNA mutations were responsible for these phenotypic variations, the complete mitochondrial genomes of both cell lines were directly sequenced. Two novel mtDNA mutations were identified within cytochrome c oxidase subunit II (COXII) and the d-loop of 2008 and C13* cells respectively, however the functional significance of these defects were not obvious. To expunge the effects of nuclear DNA (nDNA) cybrids were created by transferring the mtDNA of 2008 and C13* cells to a common 143B TK⁻ nDNA background, creating 2008cyb and C13cyb cells. C13*cyb cells did not demonstrate CDDP resistance, decrease in rate of oxygen consumption or increase in ΔΨₘ when compared to 2008cyb cells. However, C13*cyb cells did retain mitochondrial morphological properties as well as increased Rh123 sensitivity and ROS production. This data would imply that mtDNA mutations are responsible for a proportion of mitochondrial-associated changes in the context of carcinogenesis.
Mitochondrial DNA Mutations in Cancer
Keywords: phenotype; DNA; mitochondria; cancer